Post-Socialist Czech Education Research on Socially Disadvantaged/Roma Children and Families: Literature Review - Jana Obrovská; Kateřina Sidiropulu Janků (Karolinum Press, 2020)
The literature review analyses papers presenting results of original empirical research on the education of socially disadvantaged/Roma children and families that was conducted in the Czech Republic between 1989 and summer 2017. Our intention to elaborate this study was to make the existing research results and procedures accessible to the international scientific community, but also to support further development of the field, including disciplinary intersections and cooperation among different research institutes. After searching through seven research databases and using knowledge of the research field, 57 studies were selected for further analysis. The review study presents five research question categories focusing on the development of the selected research field, prevailing topics/themes that are researched, research settings in which the data were collected, main methodological approaches, and primary research subjects/objects. The results of our analysis pinpoint dynamic development not only in the relevant research field but also in the practice and educational policies concerned. From the methodological point of view, the slight predominance of qualitative research procedures in the field is evident. Nevertheless, there is a pervading lack of reflexivity towards the lived world of the research participants − mainly Roma children and families − and a preferred focus on macro and mezzo levels in the research scopes. The most influential published research in the field was identified, as was cross-referencing habits. In general, productivity, as well as cross-referencing culture, have developed more intensely since 2009. In conclusion, we suggest further development in both the practice of research, as well as the development of databases, so more integrative work may support tackling education inequalities in the Czech Republic.